Procedural Justice and Affective Commitment: An Organizational Trust Mechanism - Aldi Kusnandar; Sri Wahyuni (Yayasan Education Al Aqsho Modern, 2022)
The purpose of this study was to determine the effect of procedural justice on performance with organizational trust as a mediating variable. The population is the State Civil Apparatus of Indragiri Hilir Regency with a sample of 140 people. Data collection techniques using questionnaires and distribution using google form. Technical analysis of the data in this study is Structural Equation Modeling (SEM) using WarpPLS 7.0 for data processing. The result of this study is that procedural justice has an effect on the affective commitment of ASN to the Indragiri Hilir Regency Government. Procedural justice affects the trust of ASN organizations in the Indragiri Hilir Regency Government. Organizational trust affects the affective commitment of ASN to the Indragiri Hilir Regency Government. Procedural justice affects the affective commitment of ASN to the Indragiri Hilir District Government through organizational trust.